(untitled) (Research, Society and Development, 2022)
Obesity is a worldwide public health problem that favors chronic noncommunicable diseases that affect the quality of life and the risk of death. Therefore, it’s necessary to combat this epidemic through loss of body weight. Carbohydrate restricted diets are the subject of questions about efficacy, mechanism of action and adverse effects. Under this definition there is a dietary protocol that has a severe restriction on carbohydrates, the ketogenic diet, which was originally indicated for the non-pharmacological treatment in epilepsy, has currently been indicated for weight loss without a consensus in the literature . The objective of this work was to carry out a narrative review of literature on the ketogenic diet as to its efficiency in weight loss, metabolic repercussions, sports performance and side effects. Twenty-six scientific articles published in the last fourteen years available in the portals PubMed, Scielo, Google Academic, BioMed was selected. In 24 studies there was participation of control group. In 18 articles the participants were submitted to protocols without caloric restrictions. In all the studies, weight reduction of the participants was verified. After the review, it’s considered that the ketogenic diet is effective in weight loss, improves certain biochemical parameters, but when the calories are controlled the results in weight loss tend to be similar to a control diet, although there are differences in serum biochemistry.